Bio–psycho-socio-spirituální pohled na rodinu optikou probačního programu - Brodská, Taťána (Univerzita Pardubice, 2010)
We start with an assumption a human being lives in various systems and every individual becomes a part of them. A "defect" in one particular part influences the whole system, which responds retrospectively to the way of its remedy. This is a way we try to cooperate also with a family of a juvenile offender within the framework of a probation programme or any alternative programme - alternative educational measures.
Keywords: probation programme; offender; alternative educational measures; probation and mediation service; social and legal children's protection department; guardian - probation officer